1984
DOI: 10.1007/bf02257375
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective aminoacylation of a dinucleoside monophosphate by the imidazolides ofDl-alanine and N-(tert-butoxycarbonyl)-Dl-alanine

Abstract: The aminoacylation of diinosine monophosphate (IpI) was studied. When the acylating agent was the imidazolide of N-(tert-butoxycarbonyl)-DL-alanine, a 40% enantiomeric excess of the L isomer was incorporated at the internal 2' site and the positions of equilibrium for the 2' in equilibrium with 3' migration reaction differed for the D and L enantiomers. The reactivity of the nucleoside hydroxyl groups decreased in the order 2'(3') greater than internal 2' greater than 5', and the extent of reaction was affecte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
23
0

Year Published

1987
1987
2016
2016

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 68 publications
1
23
0
Order By: Relevance
“…1). The feasibility of esterification at the internal 2Ј hydroxyl is demonstrated by previous work showing that reaction of dinucleotides with activated amino acids gives acylation at the internal 2Ј and terminal 2Ј(3Ј) positions in ratios ranging from 1:9 to 6:4, depending on the dinucleotide and the buffer concentration (38)(39)(40). The esterification reaction need not be specific, because reactions between an ␣-keto acid and a dinucleotide that cannot catalyze the first step in a synthetic pathway will simply lead to dead-end products.…”
Section: A Model For Catalysis Of Amino Acid Synthesis By Dinucleotidesmentioning
confidence: 99%
“…1). The feasibility of esterification at the internal 2Ј hydroxyl is demonstrated by previous work showing that reaction of dinucleotides with activated amino acids gives acylation at the internal 2Ј and terminal 2Ј(3Ј) positions in ratios ranging from 1:9 to 6:4, depending on the dinucleotide and the buffer concentration (38)(39)(40). The esterification reaction need not be specific, because reactions between an ␣-keto acid and a dinucleotide that cannot catalyze the first step in a synthetic pathway will simply lead to dead-end products.…”
Section: A Model For Catalysis Of Amino Acid Synthesis By Dinucleotidesmentioning
confidence: 99%
“…Stereoselective reactions, which could have served as bases for the origin and evolution of the protein-synthesizing system, would seem more fruitful subjects of study. In that vein Profy and Usher (4,5) have shown some stereoselectivity for the L isomer in esterification reactions with amino acids and oligo-or polynucleotides. They also have discussed in some detail the fact that amino acids esterified to ribonucleotides constantly migrate between the 2' and 3' positions ofthe ribose and have emphasized the possible significance of studies on the differential distribution of D and L amino acids between the 2' and 3' positions.…”
mentioning
confidence: 99%
“…A handful of investigators have previously demonstrated preferred binding of various L-amino acids to their D-(anti)codons (30)(31)(32)(33) The current hypothesis makes the unique, and currently untested, prediction that D-amino acids should have equal affinity for the directionally inverse L-(anti)codons. Thus, if L-methionine prefers D-AUG, D-methionine will prefer L-GUA, not L-AUG (see section on Stereochemistry, directionality and affinity, above).…”
Section: Experimental Testsmentioning
confidence: 89%
“…(3) Some amino acids bind to some polynucleotide sequences with higher affinity than other possible pairings. (10)(11)(12)(13)(14)(15)(16)(17)(30)(31)(32) . Since binding of compounds buffers each compound structurally and chemically from reactions and degradation processes, the higher the affinity a pair of compounds had, the greater the likelihood that their complex, or the components of their complex, would survive to participate in the formation of the genetic code.…”
Section: Stereochemistry Directionality and Affinitymentioning
confidence: 99%